Languages, methodologies, and development tools for multi-agent systems Third International Workshop, LADS 2010, Lyon, France, August 30 - September 1, 2010, Revised Selected Papers - Dastani, Mehdi; Fallah Seghrouchni, Amal; Hübner, Jomi; Leite, João (Lecture Notes in Computer Science, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the Third International Workshop on Languages, Methodologies, and Development Tools for Multi-Agent Systems, LADS 2010, held in Lyon, France, in August/September 2010, as part of MALLOW, a federation of workshops on Multi-Agent Logics, Languages, and Organizations. The 8 revised full papers presented were carefully selected during two rounds of reviews from 11 initial submissions. The papers address issues related to theories, methodologies, models and approaches that are needed to facilitate the development of multi-agent systems ensuring their predictability and verification.